NEUTRON DETECTION AROUND HIGH ENERGY MEDICAL ELECTRON LINEAR ACCELERATORS - Poje, Marina (Array, 2012)
High energy electron linear accelerators have a wide use in radiation therapy. When photon beams with photon energy higher than 10 MeV are used, unwanted neutrons can be produced in giant dipole resonance reaction between photon beam and accelerator’s head material (led, tungsten). In this reaction an isotropic flux of neutrons is produced, dominated by neutrons with energies between 700 keV and 1 MeV. Characterisation of full radiation field is important to correctly evaluate exposure of patients and medical personnel. The detection of neutrons was made around 15 MV photon beams of Siemens Mevatron MD2 and Siemens Oncor Impression as well as around 18 MV photon beams of 2 Siemens Oncor Expression linear accelerators. Measurements were performed by nuclear track etched detectors CR-39 associated with converter (radiator) that consist of 10B and with an active neutron detector Thermo BIOREM FHT 742. Detectors were set at several locations to evaluate neutron ambient dose equivalent and/or neutron dose rate to which either medical personnel or patients could be exposed. Also, neutron dose dependence on collimator aperture was analysed. The rooms of two linear accelerators, (with 15MV and 18 MV high energy beams), were built in the place of decommissioned 60Co units, so the main limitation was the space. Therefore, the mazes are very short and the plates of steel in combination with concrete were used for shielding, making the neutron flux more pronounced. In both rooms built intentionally for accelerators, the neutron exposure to the personnel was significantly lower. Measured values at the beam isocenters were comparable with the published ones, showing from 2 to 4 times higher neutron dose equivalent in 18 MV beams than in 15 MV beams. Neutron fluence increased with field size having the maximum at 20 cm x 20 cm, and then decreased with wider collimator apertures.